2001
DOI: 10.1103/physrevb.64.045103
|View full text |Cite
|
Sign up to set email alerts
|

Finite-temperature numerical renormalization group study of the Mott transition

Abstract: Wilson's numerical renormalization group (NRG) method for the calculation of dynamic properties of impurity models is generalized to investigate the effective impurity model of the dynamical mean field theory at finite temperatures. We calculate the spectral function and self-energy for the Hubbard model on a Bethe lattice with infinite coordination number directly on the real frequency axis and investigate the phase diagram for the Mott-Hubbard metal-insulator transition. While for T < Tc ≈ 0.02W (W : bandwid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
301
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 285 publications
(331 citation statements)
references
References 50 publications
(104 reference statements)
29
301
0
1
Order By: Relevance
“…This behavior has been detected experimentally by photoemission experiments [77]. Altogether, the thermodynamic transition line U c (T ) corresponding to the Mott-Hubbard MIT is found to be of first order at finite temperatures, and is associated with a hysteresis region in the interaction range U c1 < U < U c2 , where U c1 and U c2 are the interaction values at which the insulating and metallic solution, respectively, vanish [33,37,78,79,76,80]. As shown in Fig.…”
Section: Dmft and The Three-peak Structure Of The Spectral Functionmentioning
confidence: 72%
See 1 more Smart Citation
“…This behavior has been detected experimentally by photoemission experiments [77]. Altogether, the thermodynamic transition line U c (T ) corresponding to the Mott-Hubbard MIT is found to be of first order at finite temperatures, and is associated with a hysteresis region in the interaction range U c1 < U < U c2 , where U c1 and U c2 are the interaction values at which the insulating and metallic solution, respectively, vanish [33,37,78,79,76,80]. As shown in Fig.…”
Section: Dmft and The Three-peak Structure Of The Spectral Functionmentioning
confidence: 72%
“…The inset shows the U dependence of A(ω = 0), in particular the rapid decrease for U ≈ 1.1 W ; from Ref. [76].…”
Section: Dmft and The Three-peak Structure Of The Spectral Functionmentioning
confidence: 99%
“…One such method is the numerical renormalization-group (NRG) [42,43,[46][47][48]. It consists of a logarithmic discretization of the continuum of states of the conduction-band electrons, followed by a mapping to a one-dimensional chain Hamiltonian with exponentially decreasing hopping constants.…”
Section: Model and Methodsmentioning
confidence: 99%
“…This peak smoothly disappears upon further increasing the temperature and at T = 1/5 only two broad Hubbard bands remain in the spectrum reminiscent of the Mott insulator above the critical temperature of the metal-insulator transition. 27 In Ref. 4 it was shown that this insulator-to-bad-metal crossover is reflected also in the dc and ac conductivity and is accompanied by a substantial increase of the spin susceptibility which follows the Curie-Weiss law at high T .…”
Section: A Phase Diagrammentioning
confidence: 99%
“…In the V = 0 limit we have two decoupled copies of a single-band Hubbard model with semi-circular density of states, a problem which has been extensively studied within DMFT. 23,27 It is well known that upon increasing the interaction strength U at finite, low temperature the paramagnetic phase undergoes a discontinuous transition from a metal to a MI with a hysteresis in the interval U c1 < U < U c2 . 27 At high temperatures the hysteretic behavior is replaced by a continuous crossover.…”
Section: A Phase Diagrammentioning
confidence: 99%